The impact of ergonomic practices toward employee's performance in an organization / Nurshafiqa Musa - Musa, Nurshafiqa (2014)
Ergonomics or human factors was the scientific discipline concerned with the understanding of interactions among humans and other element of a system, and the profession that applies theory, principles, data and methods to design in order to optimize human well-being and overall system performance (International Ergonomic Association, 2000). Ergonomic was the interaction between employee and the equipment they use and the environment they involve in. The employee's performance was maximized if the workstations and work methods are well-designed. Ergonomic improves health and safety, reduce cost and absenteeism and also ensures to meet the social and legal obligations of employers to their employees. Workplace ergonomic plays an important role in increasing the employee's performance. Employee's performance has relationship with the ergonomic practices at workplace. The unsafe and unhealthy condition may lead to poor performance of employee. The ergonomic consideration includes the office layout, office furniture and also office equipment. This consideration must be tailored to develop good working environment and better performance because an acceptable working condition and equipment help the employees perform job effectively.